Scale up business strategy through the development of the frozen food products industry at ubi manis restaurant linggarjati - Setiawati, Ety; Dewi, Ratna Puspita (Journal of Gastro Tourism, 2025)
The development of the restaurant business in 2024 is growing very rapidly, so that the competition in the restaurant business is becoming increasingly competitive. To anticipate a decline in revenue and business continuity, a strategy is needed to anticipate these conditions. Ubi Manis Restaurant wants to find other business alternatives, besides serving guests who come to the restaurant. Food products at Ubi Manis Restaurant have great potential to be developed into a small-scale frozen food industry. Bitter ballen is one of the snack products that has the potential to become frozen food. The research method used is qualitative with thematic analysis methods, to analyze data with the aim of identifying patterns, or to find themes through the data that has been collected. The result of the research that is expected through the frozen bitter ballen product development strategy is that the Ubi Manis restaurant will be able to expand the scale of business, especially in the Kuningan, Majalengka and Cirebon areas, so that the existence of the Ubi Manis restaurant can be sustainable.